2014
DOI: 10.19026/rjaset.7.774
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Graphics Education: Webcomics as a Tool to Improve Weaker Students' Motivation

Abstract: In engineering colleges, first-year students come from different kinds of high school and have different technical backgrounds. In engineering graphics courses, the weaker students are the ones entering with a lower technical background. Such students are less motivated and have generally difficulties in keeping high their attention level during the lessons. In this study, the use of a webcomics structured in graphic novels was experimented as a motivational support in an engineering graphics course. Sixty nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…1 A literature survey on innovative teaching revealed that among various proposals, some authors suggest the use of comics as an introduction to lectures in order to win student interest. [2][3][4] Given the number of recent works found in the literature it seems that gamification is another trend of growing interest. With reference to the literature, 5 the gamification of learning is defined as an approach to motivate students to learn by using game elements in learning environments.…”
Section: Introductionmentioning
confidence: 99%
“…1 A literature survey on innovative teaching revealed that among various proposals, some authors suggest the use of comics as an introduction to lectures in order to win student interest. [2][3][4] Given the number of recent works found in the literature it seems that gamification is another trend of growing interest. With reference to the literature, 5 the gamification of learning is defined as an approach to motivate students to learn by using game elements in learning environments.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, using this approach, the already developed and validated TD tools are the exercise workbook (Figure a) ; the Technical Drawing Learning ToolsLevel 2—TDLT—L2 (Figure b) which is a self‐learning tool designed to better understand the different dimensioning types and related concepts , and the webcomic stripe “The adventures of Mr. Clumsy, the engineer” (Figure c) as a tool to improve students' motivation and their participation during the TD lessons .…”
Section: Tdeg Integrated Frameworkmentioning
confidence: 99%
“…For example, comic book stories can be useful to break the ice with the most struggling students. As Metraglia et al (2014) say, comics tell the typical work situations in a funny way, or they help self-recover prerequirements gaps (Baronio et al 2016). The most advanced instruments tested by Violante et al (2016) for online learning environments with three-dimensional functions should also be evaluated.…”
Section: Introductionmentioning
confidence: 99%